Destabilization of Yellow Mustard Emulsion Using Organic Solvents. (26th January 2013) - Tabtabaei, Solmaz; Ataya Pulido, Veronica M.; Diosady, Levente L.
Abstract: An aqueous extraction process was developed consisting of aqueous contact with dehulled yellow mustard flour to recover protein followed by dissolution of the released emulsion in dimethylformamide (DMF) or isopropyl alcohol (IPA) to recover the released oil in the form of single‐phase oil–solvent miscellae suitable for industrial applications. Only some 38 ± 3 % of the oil in the yellow mustard emulsion was extracted using DMF even at high weight ratios since DMF is widely miscible with water, preventing separation of the oil from the emulsion. A ternary phase diagram of DMF/oil/water was prepared and confirmed the limited solubility of the oil in DMF in the presence of water. The use of 31:1 IPA:oil weight ratio could effectively recover over 94 % of the oil in the emulsion; however, multiple‐stage treatment of the emulsion was proven to be more efficient with lower volumes of IPA required to achieve high oil extraction yields. The results suggest that the optimal conditions for multiple‐stage process were four stages using 2:1 IPA:oil weight ratio, with 96 ± 1 % oil recovery from the emulsion.